Indole butyric acid effect on rhizogenic capacity of Eucryphia glutinosa cuttings - Latsague Vidal, Mirtha; Sáez Delgado, Patricia; Yáñez Delgado, Jéssica (Bosque (Valdivia), 2009)
Eucryphia glutinosa is an endemic species from Chile that at the present is with conservation problems, being catalogued as a rare species. Its distribution area and its population are decreasing considerably due to deforestation. The objective of the present work was to evaluate its reproductive capacity by means of cuttings rhizogenesis. Cuttings were collected during April 2007 in the National Malleco Reserve, Araucania Region. The harvested cuttings were treated with indole butyric acid (IBA) at different concentrations (0, 250, 500, 1,000 and 1,500 mg L–1) as rooting stimulator. After seven months in a hot bed a 30% of total rooting was obtained. The best results in respect of the process of rhizogenesis were shown by 500 mg L–1 IBA, with an average of 3 cm in root length and 12 roots by cutting, with a 56.5% of rooting.